FAEE exerts a protective effect against osteoporosis by regulating the MAPK signalling pathway - Ming‑Yue Wang; Meng‑Fei An; Mao-Si Fan; Shao-Shi Zhang; Ze‑Rui Sun; Yun‑Li Zhao; Ze-Min Xiang; Jun Sheng (Taylor & Francis Group, 2022)
Context Ferulic acid ethyl ester (FAEE) is abundant in Ligusticum chuanxiong Hort. (Apiaceae) and grains, and possesses diverse biological activities; but the effects of FAEE on osteoporosis has not been reported. Objective This study investigated whether FAEE can attenuate osteoclastogenesis and relieve ovariectomy-induced osteoporosis via attenuating mitogen-activated protein kinase (MAPK). Materials and methods We stimulated RAW 264.7 cells with receptor activator of NF-κB ligand (RANKL) followed by FAEE. The roles of FAEE in osteoclast production and osteogenic resorption of mature osteoclasts were evaluated by tartrate resistant acid phosphatase (TRAP) staining, expression of osteoclast-specific genes, proteins and MAPK. Ovariectomized (OVX) female Sprague-Dawley rats were administered FAEE (20 mg/kg/day) for 12 weeks to explore its potential in vivo, and then histology was undertaken in combination with cytokines analyses. Results FAEE suppressed RANKL-induced osteoclast formation (96 ± 0.88 vs. 15 ± 1.68) by suppressing the expression of osteoclast-specific genes, proteins and MAPK signalling pathway related proteins (p-ERK/ERK, p-JNK/JNK and p-P38/P38) in vitro. In addition, OVX rats exposed to FAEE maintained their normal calcium (Ca) (2.72 ± 0.02 vs. 2.63 ± 0.03, p < 0.05) balance, increased oestradiol levels (498.3 ± 9.43 vs. 398.7 ± 22.06, p < 0.05), simultaneously reduced levels of bone mineral density (BMD) (0.159 ± 0.0016 vs. 0.153 ± 0.0025, p < 0.05) and bone mineral content (BMC) (0.8 ± 0.0158 vs. 0.68 ± 0.0291, p < 0.01). Discussion and conclusions These findings suggested that FAEE could be used to ameliorate osteoporosis by the MAPK signalling pathway, suggesting that FAEE could be a potential therapeutic candidate for osteoporosis.